On uncovered interest parity puzzles: excess return, asymmetry and crash risk - Cassio Felix Jardim (2017)
This dissertation evaluates implications of the uncovered interest parity (UIP) equation for the pound/dollar nominal exchange rate variation and for the return of the carry trade investment strategy. Conditioned on interest rate differential, the exercises verified that 1) the higher thegap between British and US interest rates, the higher the conditioned standard deviation of the exchange rate return and of the carry trade strategy return; 2) the probability of extreme pound devaluation, away from a conditioned measure of centrality, is larger than that of extremeUS dollar appreciation, which is the same as saying that the probability of extreme losses for investing in British securities, under the carry trade strategy, is larger than the probability of extreme losses for investing in American securities; 3) this asymmetry increases as UK interestrates becomes larger than the US rates. Overall, the results sustain the UIP puzzle. Quantile regression was used to estimate the conditional empirical density functions and the measures of asymmetry